2021
DOI: 10.1097/gme.0000000000001762
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of menopause during incarceration

Abstract: Objective: Despite increasing representation of older women in US jail and prison facilities, their menopause experiences and access to related care remain uncharacterized. Our objective is to explore the menopause experiences of women incarcerated in jail and prison facilities. Methods: We conducted a pilot study of four semi-structured in-depth interviews with women in the community who experienced menopause symptoms while incarcerated in either a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Women who are experiencing incarceration face unique barriers to seeking menopause-related care. A recent pilot study reported challenges in accessing clinical menopause management, as well as appropriate accommodations and social support (Jaffe et al , 2021). Better understanding the challenges to pharmacologic management of menopause symptoms in carceral settings is critical, and it is also necessary to ensure more comprehensive programming to support individuals going through the menopause transition while incarcerated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women who are experiencing incarceration face unique barriers to seeking menopause-related care. A recent pilot study reported challenges in accessing clinical menopause management, as well as appropriate accommodations and social support (Jaffe et al , 2021). Better understanding the challenges to pharmacologic management of menopause symptoms in carceral settings is critical, and it is also necessary to ensure more comprehensive programming to support individuals going through the menopause transition while incarcerated.…”
Section: Discussionmentioning
confidence: 99%
“…(Gold et al , 2004; Lorvick et al , 2018; Miller et al , 2005; Monteleone et al , 2018; Nosek et al , 2012; Sauer et al , 2020; Thurston and Joffe, 2011; Tuchman, 2007; Woods et al , 2006). Additionally, carceral institutions restrict access to layered clothing, cool drinks, fans and other tools for managing menopause symptoms (Jaffe et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The incarceration rate for women has continued to climb and compared to men, aging women face distinct burdens. These include longer sentences, pronounced histories of poverty, violence and trauma, elevated levels of chronic health problems, exacerbated menstrual and menopausal symptoms and unmet needs regarding grief and loss (Bronson and Berzofsky, 2017; Handtke et al , 2015; Jaffe et al , 2021; Golembeski et al , 2020). Substantial challenges are also likely present for older gender and sexual minorities, though too little research has been completed with these persons (Maschi and Morgen, 2020; Baćak et al , 2018).…”
Section: The Mental Health Of Older Adults Who Are Incarceratedmentioning
confidence: 99%
“…This population is growing older, but incarceration among older women is rarely the focus of research, policy or programming (Aday and Farney, 2014). Yet, compared with incarcerated older men, older women experiencing incarceration are more likely to have serious health problems and significant mobility challenges (Wahidin, Noelle and Kelly, 2005; Carlen, 2006), including menopause which can exacerbate many health conditions and is itself a major health concern for one in three older women in prison (Jaffe et al , 2021).…”
Section: Community–academic Partnerships: An Opportunity To Improve T...mentioning
confidence: 99%